Conservation of tropical tree biodiversity through macropropagation by shoot cutting of raru (Cotylelobium melanoxylon), a highly utilized dipterocarp in North Sumatra, Indonesia - Arida Susilowati Susilowati; Kansih Sri Hartini; Deni Elfiati; Henti Hendalastuti Rachmat; Yosie Syadza Kusuma; M. Zulham Efendi Sinaga; Tati Suhartati (Society for Indonesian Biodiversity, 2020)
Abstract. Susilowati A, Hartini KS, Elfiati D, Rachmat HH, Kusuma YS, Sinaga MZE, Suhartati T. 2020. Macropropagation by shoot cutting of raru (Cotylelobium melanoxylon), a highly utilized dipterocarp in North Sumatra, Indonesia. Biodiversitas 21: 724-730. Cotylelobium melanoxylon (Hook.f.) Pierre, or locally named raru, is one of native tree species from North Sumatra that has many uses for its wood and medicinal purposes for anti-diabetic, anti laxative and blood coagulation. C. melanoxylon has been experiencing short supply due to its limited natural distribution, forest degradation, illegal harvesting for its wood and bark and uncertain fruiting season of the species. Along with these alterations, C. melanoxylon population has been decreasing. The objective of this research was to determine the effectiveness of C. melanoxylon propagation by shoot cutting. Randomized factorial design with 2 factors was employed in this research. The first factor (factor A) was the cutting media (i.e. topsoil only; topsoil and sand with proportion of 1:1 v/v), and the second factor (factor B) was commercial auxin addition (i.e. 1g/100cuttings; without auxin). The observed parameters were survival percentage, rooted percentage, number of primary and secondary root, length of primary and secondary root and root histology. The results showed that the interaction between media and auxin addition did not have any significant effect on all tested parameters. The average survival percentage was 70-90% and rooting percentage was 50-90%. Adventitious root formation on C. melanoxylon cutting was originated from cell differentiation on wounded area near cambium, followed by root primordia formation and root meristem formation. The success of artificial propagation technique for this species will provide basic practice of C. melanoxylon cultivation and may contribute to the effort of ex situ conservation for valuable and threatened tree species.